AKUNTANSI KULTURAL: STUDI KASUS PENCATATAN DAN PEMBIAYAAN PERKAWINAN ADAT PADA SUKU MUNA - Rika, Abdul Rachman (JURSIMA, 2025)
This study aims to analyze the traditional recording and financing system applied in the Muna tribe's traditional marriage, and to identify the underlying cultural values. The research method used is a qualitative case study approach with data collection techniques in the form of in-depth interviews, direct observation, and documentation. The results of the study indicate that the cost recording system in the Muna tribe's traditional marriage is carried out informally based on trust and family solidarity. Cultural values ​​such as mutual cooperation, togetherness, and honor also shape the structure of marriage expenditure. Cultural accounting practices in the Muna tribe's traditional marriage act as a mechanism for recording costs as well as a symbol of cultural identity that needs to be maintained.